Hubungan Kerjasama Perdagangan Internasional Antara RI-India Dalam Impor Cpo Asal Indonesia 2006-2009 - Indah Octaviani; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Thesis Entitled "A Relations Free Trade Area of Cooperation RI-India in Import CPOFrom Indonesia 2006-2009''. The results of this study indicate that a bilateral histroryIndonesia dan India to solid a relations of cooperation second country in plane a trade, jasaand investasi. The fact AIFTA on 13 August 2009 espescially Indonesia and India very affectpalm oil CPO. This can be seen with an increase in total production and export of CPO toIndia which is increasing and this increase also influence the increase in Indonesia’s CPOexports as a whole. Increase in export can not be separated from the growing demand forpalm oil especially from India which is the largest importer of Indonesian CPO. Increaseddemand in influenced by the decline in import duties to India after AIFTA. Increased demandfor palm oil from India is very encouraging increase in the national CPO production. Theform of strategic partnership got the biggest opportunity in increasing cooperation of tradeIndonesia and India in plane of agriculture that is CPO. The signatured of agreement date on20 February 1992 got the princple a relations of cooperation in plane of agricultureIndonesia and India. This Form of cooperation to figure a policy to strong a trade ofcooperation Indonesia and India.Key words: Import CPO, Strategic Partnerships, AIFTA, Free Trade Area of Cooperation,MOU